Ecopedagogy and Environmental Literacy in Research Trends in Indonesia - Amaliati, Siti; Rusydiyah, Evi Fatimatur; Bakar, M.Yunus Abu (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study analyzes the trend and development of eco-pedagogy literacy in Indonesia from 2016 to 2024. The method used was a Systematic Literature Review (SLR) with the PRISMA protocol, analyzing 27 articles that met the inclusion criteria. The results of this study showed 1) a significant increase in the number of publications related to eco pedagogy literacy, especially publications in 2023, 2) Qualitative research with high school students as subjects and questionnaires as research tools are often used, 3) Problem-Based Learning (PBL) and Contextual Learning (CL) are the most common learning strategies applied in eco pedagogy. In addition, environmental awareness is the theme most often associated with ecopedagogy literacy in Indonesia. The study also revealed that the Research and Development (RnD) approach is rarely applied, so there are opportunities for developing innovative learning modules and educational media that are more interactive in introducing eco-pedagogy. This research contributes to understanding how environmental education can be strengthened through eco pedagogy and encourages further research that focuses on using technology in learning to improve environmental literacy. As such, the findings are highly relevant to supporting the development of more sustainable education programs in Indonesia.